DAMPAK EKSPLOITASI AIR TANAH SECARA BERLEBIHAN TERHADAP PEMENUHAN KEBUTUHAN AIR PENDUDUK DI DESA RAENYALE, KECAMATAN SABU BARAT KABUPATEN SABU RAIJUA - Wewo, Citra Liliani; Samin, Mikael; Hasan, Muhammad Husain (Jurnal Geografi, 2023)
This study aims to determine (1) the impact of excessive exploitation of groundwater on the fulfillment of groundwater for residents in Raenyale Village (2) Strategies for overcoming the impact of excessive exploitation of groundwater on meeting the water needs of residents in Raenyale Village.The method used in this study is a quantitative descriptive research method to test hypotheses using statistical data tests. In this study there were 103 people who became the research sample consisting of people who used drilled wells, people who used dug wells and the head of Raenyale Village. Data collection methods used are questionnaires, interviews, observation and documentation. The results showed that (1). The impact of groundwater exploitation in Raenyale Village is that there are 17 dug wells which are experiencing drought due to excessive use of drilled wells which means that the community is forced to incur additional expenses by buying tanked water to meet the population's water needs. (2). The strategy for overcoming the impact of groundwater exploitation is that there are 13 people who make infiltration wells, plant trees around the well area and with community awareness and understanding of the importance of sustainable development and use of groundwater.